Anominity and Transformation of Social Interaction in Digital Society: A Case Study of Social Media - Anggi Yus Susilowati (Journal of Religion and Social Transformation, 2025)
This research analyzes the role of anonymity as a major catalyst in the transformation of social interaction in digital society, with a case study on social media. Using a descriptive-analytical desk research method, this study examines current scientific literature to reveal the positive and negative impacts of anonymity on the dynamics of online communication. The results show that anonymity facilitates freedom of expression and the formation of inclusive virtual communities, and supports whistleblowing. However, its negative impact is more dominant, triggering online disinhibition that leads to anti-social behaviors such as cyberbullying, hate speech, and identity manipulation. Anonymity is also a key factor in the spread of disinformation/hoaxes, exacerbating opinion polarization through echo chambers, and contributing to mental health problems due to online harassment. The long-term implications include the erosion of trust and the loosening of online social norms. In conclusion, anonymity is transforming social interactions in digital society as a double-edged sword. While it offers the potential for freedom of expression and unique communities, the risks to accountability, security and digital well-being are immense. Therefore, this study emphasizes the urgency of finding a balance between facilitating the freedom of anonymity and building a healthier and more responsible online interaction environment.